Long-term study on the nitrogen retention potential of bark extracts and a polymer based thereof in cattle manure slurry. (June 2022) - Sepperer, Thomas; Petutschnigg, Alexander; Steiner, Konrad
Abstract: The addition of tree bark extracts, commercial tannin powder and a tannin-based polymer to cattle manure was investigated for its influence on the gaseous emission and nitrogen conservation potential for 28 days. In lab trials with ammonia solution as reference, the retention of ammonia was 13%, 40% and up to 65% for untreated solution, spruce bark extract and chestnut tannin respectively. The gaseous emission from manure was reduced by 40%, 58% and 66% for chestnut tannin and spruce bark extract, larch bark extract and the tannin polymer, and oak tannin, respectively. For long-term nitrogen loss mitigation, 20% more nitrogen was preserved when spruce or larch bark extract or oak tannin was added to the manure compared to the reference measurements. A combination of the pH lowering effect of tannins and covalently bonding ammonia to flavonoid hydroxy groups provides a viable method for reduction of nitrogen loss in cattle manure. Graphical abstract: Unlabelled Image Highlights: European tree bark extracts show up to 60% less ammonia emission from manure. Tannin-based polymer can effectively preserve 40% of ammonia in solution for 24 h. Condensed tannins can covalently bind ammonia and retain nitrogen in manure.